2022
DOI: 10.33596/coll.97
|View full text |Cite
|
Sign up to set email alerts
|

Rural Community Engagement for Mental Health

Abstract: Community-engagement strategies have been used successfully in mental health research and have been proposed as ideal for addressing stigma associated with mental illness. However, little has been published about using a community-engaged approach to address mental health and associated stigma in rural communities. We aimed to develop a mental health patient-centered research community and advisory board for two rural communities in Michigan with the long-term goal of improving mental health care, self-managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(20 reference statements)
0
0
0
Order By: Relevance
“…A recent systematic review (Russell et al , 2023) determined that there were only six studies worldwide that implemented community engagement methods when addressing mental health in rural and remote communities (Barnard et al , 2004 ; Barry et al , 1999 ; Bryant et al , 2015 ; Chomat et al , 2019 ; Stacciarini et al , 2011 ; Thirlwall and Whitelaw, 2019). Additional studies (Kelter et al , 2022 ; Lavrencic et al , 2021) have recently been identified that implement community engagement on this topic and population. Although there were similarities from the studies included in the literature review and the two additional studies, such as population and locations, community engagement strategies varied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review (Russell et al , 2023) determined that there were only six studies worldwide that implemented community engagement methods when addressing mental health in rural and remote communities (Barnard et al , 2004 ; Barry et al , 1999 ; Bryant et al , 2015 ; Chomat et al , 2019 ; Stacciarini et al , 2011 ; Thirlwall and Whitelaw, 2019). Additional studies (Kelter et al , 2022 ; Lavrencic et al , 2021) have recently been identified that implement community engagement on this topic and population. Although there were similarities from the studies included in the literature review and the two additional studies, such as population and locations, community engagement strategies varied.…”
Section: Introductionmentioning
confidence: 99%
“…All were conducted in rural communities of the USA, the UK, Guatemala and Australia, with the population ranging from 1,000 to 4,000 people. Collectively, these studies all implemented varying evidence-based models for community engagement, and included community-built approaches (Barnard et al , 2004; Barry et al , 1999) and participatory action research (Bryant et al , 2015; Chomat et al , 2019; Stacciarini et al , 2011; Thirlwall and Whitelaw, 2019; Kelter et al , 2022; Lavrencic et al , 2021). However, only two of the studies (Stacciarini et al , 2011; Thirlwall and Whitelaw, 2019) progressed to community empowerment, where locals were able to address mental health by independently influencing one another (Wilson and Sanyal, 2013).…”
Section: Introductionmentioning
confidence: 99%